ANALYSIS OF VALUES IN A COLLECTION OF GAYO FOLKTALES AND THEIR RELEVANCE TO INDONESIAN LANGUAGE LEARNING IN SENIOR HIGH SCHOOL 11 TAKENGON - Yusrawati Jr Simatupang; Ria Nur Fadilah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The purpose of this research is to know and describe in the form of analysis of values in the collection of Gayo folklore and its relevance to Indonesian language learning at SMA Negeri 11 Takengon. descriptive research type with a qualitative approach using the research method of library study (Library Research). The data source in this research is the book of Gayo folklore collection which will be used as the object of research. Other data sources used in this research are the head of traditional leaders, Indonesian language teachers, and students of class X SMA Negeri 11 Takengon. This research uses fifteen Gayo folktales. The values contained in the Gayo folktales studied were analyzed using Wicaksono's (2014) theory of types of language styles, namely educational values, religious values, moral values, character education values, and cultural values. The results of this study are ten data forms of educational values, six data forms of religious values, nineteen data forms of moral values, three data forms of character education values, and fifteen data forms of cultural values. Based on the findings that the researchers have examined, it can be concluded that the most dominant values in Gayo folktales are moral values. The relevance of the collection of Gayo folktales to Indonesian language learning in high school, especially SMAN 11 Takengon, is that this story can be used as teaching material at school, because using this story can facilitate students and teachers in carrying out the learning process, especially in folklore material (hikayat) on KD 3.7, 3.8, and 3.9.